1996
DOI: 10.1177/02841851960373p2102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ionic and Nonionic Contrast Media on Endothelium and on Arterial Thrombus Formation

Abstract: Iodixanol appears to be most biocompatible with endothelium, and has a moderate inhibitory effect on fibrin deposition in flowing blood. This differs from iohexol, and in particular from ioxaglate, which induce endothelial changes in morphology with no effect on fibrin deposition. Since none of the CM affected the platelet aggregate formation, and since ioxaglate has been reported to have stronger anticoagulant and antithrombotic properties than iodixanol or iohexol in in vitro assays, it is apparent that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The nonionic isosmolar dimer iodixanol appears to have less thrombogenic potential and more favorable effects on endothelial cells than the nonionic low osmolar monomer iohexol [14]. However, iodixanol has been reported to increase platelet aggregation, whereas ioxaglate inhibits it [9].…”
Section: Discussionmentioning
confidence: 97%
“…The nonionic isosmolar dimer iodixanol appears to have less thrombogenic potential and more favorable effects on endothelial cells than the nonionic low osmolar monomer iohexol [14]. However, iodixanol has been reported to increase platelet aggregation, whereas ioxaglate inhibits it [9].…”
Section: Discussionmentioning
confidence: 97%
“…CM normally induces dilation in healthy subjects [82,83], however, in CAD patients who typically exhibit endothelial dysfunction, coronary vasoconstriction or even vasospasm may occur [83,84]. In vitro studies have demonstrated that CM may exert negative effects on both EC [85,86] and VSMC [87,88]. CM is more likely to exert dose-dependent [89] vasoconstriction in segments close to a stenotic lesion [83,90], emphasizing a possible involvement of endothelial dysfunction, and constriction occurs more frequently following ionic CM than the currently used non-ionic CM [91].…”
Section: Does Contrast Media Using During Ptca/pci Cause Vascular Dysmentioning
confidence: 99%
“…The contrast medium used in our angiographies was Omni-paque® 300 (GE Healthcare, CO/ Cork, Ireland), a low osmolar, non-ionic contrast medium containing 647 mg of the active substance Iohexol per milliliter. Iohexol induces arterial endothelial changes in morphology with no effect on fibrin deposition 15 . Formed thrombi will be larger and more resistant to thrombolysis compared to saline controls 16 .…”
Section: A B D Cmentioning
confidence: 99%